Familial Aggregation of Candidate Phenotypes for Borderline Personality Disorder - Ruocco, Anthony C. (Personal Disord, 2014)
Borderline personality disorder (BPD) and its core DSM factor-analytically derived phenotypes aggregate in families. To potentially inform future conceptualizations of BPD, this study examined the familial aggregation and coaggregation with BPD of three additional candidate phenotypes for BPD psychopathology: anxiousness, aggressiveness and cognitive dysregulation. Participants included 347 probands (126 with BPD, 128 without BPD, and 93 with major depressive disorder) and 814 parents and siblings of probands. All participants completed diagnostic assessments and scales assessing the candidate phenotypes. The familial aggregation of phenotypes (correlation of level of phenotype between family members), the familial coaggregation of phenotypes with BPD (correlation of phenotype with BPD between family members), and the within-individual correlation of phenotypes with BPD were assessed. All three candidate phenotypes showed high levels of familial aggregation (r’s = .14 – .53, p’s < .001), the magnitudes of which were comparable to DSM-based core sectors of psychopathology. Anxiousness and cognitive dysregulation showed strong within-individual associations with BPD (r’s = .55 and .46, respectively; p’s < .001) and substantial familial coaggregation with BPD (r’s = .12 and .13, respectively; p’s ≤ .002). In contrast, aggressiveness showed a weak within-individual association with BPD (r = .11, p = .12) and little familial coaggregation with BPD (r = .05, p = .21). These findings suggest that anxiousness and cognitive dysregulation are promising phenotypes for BPD psychopathology that move beyond factor-analytically based conceptualizations. In contrast, aggressiveness was only weakly related to BPD, suggesting that this phenotype may not represent an essential feature of this disorder.